The sex-age ratio, diving behaviour and habitat use of Goldeneye Bucephala clangula wintering in northeast Scotland - Duncan, Keith; Marquiss, Mick (Wildfowl, 1993)
Goldeneye were counted on lochs, rivers and at the coast of northeast Scotland from 1988 to 1990. Wintering birds arrived in October and November and left in April. Arrival times at communal overnight roosts suggested that daylength might have limited foraging time in the shortest days of winter. Mid-winter changes in the numbers at daytime foraging sites, but not at overnight roosts, suggested that the population shifted from feeding on lochs to the lower parts of rivers and to the coast as the winter progressed. Changes in the proportion of adult males in foraging flocks was consistent with such shifts. Overall, foraging flocks at lower elevations, particularly on the coast and the lower sections of rivers, contained more adult males. Adult males dived for longer than females, particularly at estuary foraging sites. It is argued that adult males have a competitive advantage over females where benthic foods are concentrated in deep or fast flowing water, but that some such sites retain good feeding for longer, and are thus increasingly used by more Goldeneye (including females and first year birds) as the winter progresses. The total population in the area was estimated at between 700 and 850. More than half of these frequented the lower parts of rivers, which should now be considered for ’Nationally Important’ status for wintering Goldeneye.